1998
DOI: 10.1021/jm970180w
|View full text |Cite
|
Sign up to set email alerts
|

Development of a Three-Dimensional CysLT1 (LTD4) Antagonist Model with an Incorporated Amino Acid Residue from the Receptor

Abstract: This paper describes the molecular modeling of leukotriene CysLT1 (or LTD4) receptor antagonists. Several different structural classes of CysLT1 antagonists were superimposed onto the new and highly rigid CysLT1 antagonist 8-carboxy-3'-[2-(2-quinolinyl)ethenyl]flavone (1, VUF 5017) to generate a common pharmacophoric arrangement. On the basis of known structure-activity relationships of CysLT1 antagonists, the quinoline nitrogen (or a bioisosteric equivalent thereof) and an acidic function were taken as the ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2004
2004
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(14 citation statements)
references
References 47 publications
1
13
0
Order By: Relevance
“…One of the difficulties in the development of a reliable 3D pharmacophoric model for CysLT1 antagonists resides in the flexibility of most antagonists. Furthermore, despite the fact that several antagonists share identical structural elements with the agonists (and a common binding site for agonists and antagonists has been proposed), the existence of structural overlapping between different classes of CysLT receptor antagonists and/or agonists is still debatable [68]. Based on quantitative SAR studies (QSAR), an hypothetical computational model of CysLT1 pocket has been built using almost rigid leukotriene antagonists as template; an arginine residue is incorporated into the preliminary model as an interaction site for the acidic moieties of antagonists [68].…”
Section: Resultsmentioning
confidence: 99%
“…One of the difficulties in the development of a reliable 3D pharmacophoric model for CysLT1 antagonists resides in the flexibility of most antagonists. Furthermore, despite the fact that several antagonists share identical structural elements with the agonists (and a common binding site for agonists and antagonists has been proposed), the existence of structural overlapping between different classes of CysLT receptor antagonists and/or agonists is still debatable [68]. Based on quantitative SAR studies (QSAR), an hypothetical computational model of CysLT1 pocket has been built using almost rigid leukotriene antagonists as template; an arginine residue is incorporated into the preliminary model as an interaction site for the acidic moieties of antagonists [68].…”
Section: Resultsmentioning
confidence: 99%
“…4) for the leukotriene agonists/antagonists, namely, (1) a lipophilic anchor (side chain), (2) a central flat unit (triene), (3) an ionic pocket (peptide and/or carboxylic acid group), and (4) a hydrophilic site (acidic group). Since this description, other workers have further refined this conceptual model to a three-dimensional one [44,45,46,47]. Interestingly, the three-dimensional models have suggested that all CysLT 1 antagonists may not bind to the same site or in the same manner as the endogenous ligand.…”
Section: Eicosanoid Ligand Modificationsmentioning
confidence: 99%
“…Among them, 2‐alkenylquinoline scaffold possess significant bioactivities, as exemplified in Figure . For instances, Montelukast (A 1 , drug for asthma), VUF 5017 (A 2 , CysLT1 antagonist), Chimanine B (A 3 , antileishmanial activity), (A4, FZ‐41) and (A4, KHD161) are utilized in AIDS therapy due to their ability as HIV integrase inhibitors. Additionally, the 2‐styryl quinolines showed anticancer (A 6 &A 7 ) and antifungal (A 8, A 9 ), antiproliferative activity (A 10 ), antifungal (A 5 , A 11 ), antimicrobial l(A 12 ) activities.…”
Section: Introductionmentioning
confidence: 99%